THE USE OF PROJECT BASED LEARNING IN TEACHING ENGLISH AT SECOND GRADE OF SMP NEGERI 1 BARRU - Widia Astuti; Andi Tenri Ampa; Ratu Yulianti Natsir (FKIP Unismuh Makassar, 2021)
The objectives of this research were to know the differences between students vocabulary achievement into class taught by using Project Based Learning and those who are taught using Direct Method in teaching English, to know the differences between students fluency achievement into class taught by using Project Based Learning and those who are taught using Direct Method in teaching English, and to know the differences significant between students’ vocabulary and fluency achievement who are taught by using Project Based Learning and Direct Method in teaching English at second grade of SMPN 1 Barru. The design of this research was Quasi Experimental Research that used one group as control class and another group as experiment class. The population of this research was the second grade of students SMPN 1 Barru, academic years 2019/2020. The sample of this research was VIII 1 and VIII 2 class, where each class consists of 20 students and the total sample were 40 students. The results of data analysis showed that the mean score of students’ vocabulary in experimental class was higher than students’ vocabulary in control class (78>66.6), and the mean score of students’ fluency in experimental was higher than students’ fluency in control class (84.1>69.9). After analyzing the data, the t-test value vocabulary and fluency in teaching English were higher than the t-table, the t-test value of vocabulary was 2.274 and the t-test value of fluency was 2.636, while the value of t-table was 2.024. It means that there was a significant difference of students’ vocabulary and fluency in teaching English between before and after using project based learning method.